1993
DOI: 10.1111/j.1471-4159.1993.tb13428.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Cationic Amino Acid Transporter (System y+) of the Rat Blood‐Brain Barrier

Abstract: Cationic amino acids are transported from blood into brain by a saturable carrier at the blood-brain barrier (BBB). The transport properties of this carrier were examined in the rat using an in situ brain perfusion technique. Influx into brain via this system was found to be sodium independent and followed Michaelis-Menten kinetics with half-saturation constants (Km) of 50-100 microM and maximal transport rates of 22-26 nmol/min/g for L-lysine, L-arginine, and L-ornithine. The kinetic properties matched that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 16 publications
8
66
0
Order By: Relevance
“…In this context, the induced nitric oxide synthesis observed in brain astrocytes was reported to be partly dependent on induction of CAT2 (20). It has also been reported that cationic amino acid transport activity across the blood-brain barrier had the kinetic properties of system y ϩ and that CAT1 mRNA was 38-fold enriched in microvessels as compared with wholebrain (42).…”
Section: Discussionmentioning
confidence: 91%
“…In this context, the induced nitric oxide synthesis observed in brain astrocytes was reported to be partly dependent on induction of CAT2 (20). It has also been reported that cationic amino acid transport activity across the blood-brain barrier had the kinetic properties of system y ϩ and that CAT1 mRNA was 38-fold enriched in microvessels as compared with wholebrain (42).…”
Section: Discussionmentioning
confidence: 91%
“…The source of L-arginine in humans and most mammals is mostly renal de novo synthesis and dietary intake, and that of L-lysine, an essential amino acid, is exclusively by dietary intake, showing that L-arginine and L-lysine must be taken up by the retina from the circulating blood. CAT1 is reported to mediate the transport of cationic amino acids at the blood-brain barrier (Stoll et al 1993;O'Kane et al 2006), implying the similar roles of CAT1 in neural tissues. Accordingly, CAT1 in neural tissues such as retina and brain is physiologically essential for satisfying the neural requirements of L-arginine and L-lysine through its functional expression at the barrier-forming cells.…”
Section: Discussionmentioning
confidence: 96%
“…d RNase protection assay on RNA from rat cerebral microvessels to assess the presence of the transporter; transport assayed by in situ brain perfusion (39).…”
Section: Characterization Of Transport Systems Involved In L-argininementioning
confidence: 99%